Frequency of Hyponatremic Dehydration in Children (02–60 Months) With Acute Watery Diarrhea in a Tertiary Care Hospital - Khan, Fayyaz; Khan, Salman Mustaan (Biological and Clinical Sciences Research Journal, 2025)
Acute watery diarrhea remains a major cause of fluid and electrolyte imbalance in young children, particularly in low-resource settings. Hyponatremic dehydration is a clinically important complication that may worsen outcomes if not identified early. Determining its frequency may help improve timely diagnosis and management. Objective: To find out the frequency of hyponatremic dehydration in children with acute watery diarrhea. Methods: This cross-sectional study was conducted in the Department of Pediatrics at Saidu Group of Teaching Hospital, Swat, from 06-January-2025 to 06-April-2025. A total of 194 children aged 2 to 60 months were selected for this study who presented with acute watery diarrhea, defined as three or more loose or watery stools within 24 hours lasting <14 days. Children with pneumonia and severe comorbidities were excluded. All the children were assessed for hyponatremic dehydration, which was diagnosed if the sodium concentration was < 135 mEq/L. Data was analyzed with SPSS 27. Results: The mean age of 194 children with acute watery diarrhea was 30.45±17.37 months, with a sodium concentration of 137.46±5.47 mEq/L. The majority of the patients were male, 121 (62.4%). Mostly were from a lower socioeconomic background, 92 (47.4%). The frequency of hyponatremic dehydration was 61 (31.4%) among these children. Conclusion: The present study observed that the frequency of hyponatremic dehydration in children with acute watery diarrhea was 61 (31.4%).